Legal and Technical Issues on Designating Archipelagic Sea Lanes Passage: Indonesia Experience - Buntoro, Kresno (Indonesian Journal of International Law, 2011)
The archipelagic sea lanes passage is a new regime of navigation. There is no much provision in the LOSC2, international law, or guidance from the international organization in how to designate an archipelagic sea lanes passage. Indonesia experienced that there are many issues left in designating the passage such as what constitute normal routes, how to apply the ten per cent rule, how to depict the axis lines, how to treat the non designated routes, what constitute ‘normal mode’. The issues also reflected in the provisions of the Indonesian Government Regulation. Although the precise form of this new navigation system has not been fully worked out, the designation of the Indonesian archipelagic sea lanes passage brings Indonesia one step closer to implementing its right over and accepting its responsibilities for its archipelagic waters. The purpose of this paper is to provide an overview of the legal and technical issues in designation of archipelagic sea lanes passage based on the Indonesia experience.